Propagule availability drives post‐wildfire recovery of peatland plant communities. Issue 3 (22nd September 2021) - Shepherd, Harry E. R.; Catford, Jane A.; Steele, Magda N.; Dumont, Marc G.; Mills, Robert T. E.; Hughes, Paul D. M.; Robroek, Bjorn J. M.
Abstract: Question: Northern peatlands are increasingly threatened by wildfire. Severe peatland wildfires can provide opportunities for new non‐peatland species to colonise post fire. Changes in plant colonisation could lead to longer‐term shifts in community composition, compromising recovery of peatland structure and function. Understanding the process of post‐fire recovery can thus inform restoration action and help restore peatland vascular plant communities. In this study, we ask: what drives initial vascular plant recovery following a peatland wildfire? Location: Stalybridge moors, England (commonly referred to as the Saddleworth moors). Methods: We used a series of vegetation surveys and seed germination experiments to identify the composition of vascular plant community one‐year post fire, along with potential propagule sources. We combined this with plant trait data and, using a series of null models, compared observed community trait values against random species assemblages. Results: Our data suggests that plant species are able to arrive at the burned site through multiple non‐exclusive recolonisation pathways. This includes colonisation through the soil seed bank, along with dispersal from surrounding unburned peatland and non‐peatland vegetation. The composition and structure of the recolonised communities was largely determined by the ability of species to reach the post‐fire site from these donor communities. This resulted in a post‐fire community composed of species possessing lower seed masses relative to the wider pool of potential colonisers. Conclusions: Our results highlight propagule availability as a driver of post‐wildfire vascular plant recovery. This provides opportunities for new non‐peatland species to colonise, potentially driving changes in the direction of vegetation recovery. Ensuring the availability of peatland species following a wildfire could therefore be key to the immediate recovery of these systems. Abstract : We investigated the drivers of initial vascular plant recovery immediately (i.e. one year) after a peatland wildfire. Our results show the composition and structure of the recolonised plant community was largely determined by propagule availability. Previously absent species could colonise the post‐fire site from the surrounding non‐peatland vegetation, which may compromise the recovery of the pre‐fire vascular plant community.